Envisioning Cyclopropane: Scientific Product or Medical Technology? - Gavrus, Delia (Scientia Canadensis, 2010)
In the late 1920s, V.E. Henderson and his team at the University of Toronto discovered the anaesthetic properties of cyclopropane. For a number of reasons, Henderson did not envision cyclopropane as a useful technology: to him it was simply a gas that possessed anaesthetic properties, rather than a potential clinical product, and this explains why cyclopropane was not first introduced into Toronto hospitals. In contrast, the practicing anaesthesiologist Ralph M. Waters envisioned cyclopropane as a medical technology, partly because it could assist his effort to professionalize anaesthesiology in the 1930s. This paper argues that it is useful to make a historically-informed distinction between cyclopropane the experimental laboratory gas and cyclopropane the medical anaesthetic because such a distinction highlights the social dimensions of the process of scientific discovery and helps illuminate the relationship between scientific production and medical technology.